Favela represented: disputes over nominations and meanings on the pages of Rio newspapers (1951-1954) - Krilow, Letícia Sabina Wermeier (Revista Crítica Histórica, 2020)
The aim of this dissertation is to analyses how the major Carioca Press (Correio da Manhã, Jornal do Brasil And Last Minute) portrayed the housing areas called favelas (favelas) during Getulio Vargas' second government (1951-1954). This work considers that, after 1945, Brazil went through an accelerated process of industrialization and urbanization. However, these processes did not occur spontaneously, but rather were conducted by a strong governmental interventionism. This interventionism brought intense changes into politic, social and economic fields, besides its consequences, not always good ones, which brought up serious questionings. When we consider that one of the most important phenomena of this time was the large increasement of the housing areas called favelas it becomes relevant to analyses how this space formation was portrayed in the press. Considering that the press has the power of legitimize (or not) ideas, it is possible to notice that the way the favelas are represented can interfere or legitimize political decisions making. This allows to glimpse that the society is trying to constitute itself, then, this theme is inserted in what Bourdieu calls symbolic struggle Is this purpose, the chosen methodology is Content Analysis.